ChemInform Abstract: Synthesis of α‐Keto‐1, 2, 3‐triazoles Through Copper Iodide Catalyzed Oxygenation. Issue 43 (21st October 2014) - Nawratil, Swantje; Grypioti, Maria; Menendez, Christophe; Mallet‐Ladeira, Sonia; Lherbet, Christian; Baltas, Michel
Abstract Copper catalyzed oxidation of benzyltriazoles with tBuOOH proceeds at room temperature to afford α‐keto‐1, 2, 3‐triazoles in good yields.